Cadmium exposure and its health effects: A 19-year follow-up study of a polluted area in China - Zhang, Wen-Li; Du, Yu; Zhai, Miao-Miao; Shang, Qi (The Science of the total environment, 2014)
Dayu County, which is located in southwestern Jiangxi Province in China, has been a cadmium (Cd)-contaminated area since the 1960s. A series of studies about Cd pollution were carried out in the 1980s. However, no further studies of the area were conducted during the following 19years. To observe cadmium (Cd) exposure levels and its health risks among residents living in contaminated areas that have been exposed to environmental cadmium pollution for 45years. Subjects involved in the survey in 1987 were interviewed again in 2006. Rice and urine samples from surviving subjects were collected to assess the level of cadmium exposure. Urinary Cd (U-Cd), urinary β2-microglobulin (U-β2-M) and urinary N-acetyl-β-d-glucosaminidase (U-NAG) were used as biomarkers to evaluate renal function. A medical examination was also performed on all subjects to diagnose clinical symptoms of Cd-exposure. Of the 96 subjects of the 1987 study who were alive in 2006, a total of 76 subjects were successfully recruited to this study. The average cadmium concentration in rice from the exposed areas was 0.59±0.41mg/kg in 2006, the average concentration of U-Cd, U-β2-M and U-NAG from cadmium-exposed areas was 25.82±0.20μg/g Cr, 6525.71±0.93μg/g Cr and 13.65±0.24μmol/g Cr, respectively, in 2006. Compared with the 1987 results, the 2006 results showed that the U-β2-M level in the exposed areas increased significantly after 19years (p<0.05). The levels of U-Cd and U-NAG did not significantly change over time. The concentration of Cd in polluted areas in 2006 is higher than it was in 1987. Renal dysfunction has worsened after 45years of continuous exposure. Thus, environmental protection and special procedures to remove cadmium in these areas require urgent consideration. •76 residents were observed in cadmium contaminated areas after 45year exposure.•Rice and urine samples were collected to assess the level of cadmium exposure.•U-Cd, U-β2-M and U-NAG were used as biomarkers to evaluate renal function.•Cd content in rice and U-β2-M level in exposed areas increased after 19years.•Renal dysfunction has worsened after 45years of continuous exposure.